A Real Time Embedded System Architecture for Autonomous Underwater Sensors Localization - Es-sadaoui, Redouane; Khallaayoune, Jamal; Brizard, Tamara (Transactions on Engineering and Computing Sciences, 2017)
Underwater Acoustic Sensor Networks (UWASNs) consist of a variable number of autonomous sensors or vehicles that are deployed over a given area to perform smart sensing and collaborative monitoring tasks. In UWASNs, sensor localization plays a critical role. Motivated by the advent of embedded systems and their widespread adoption in localization, this paper presents the design and architecture of an autonomous embedded system, that uses acoustic signal to communicate underwater. The proposed architecture implements a set of embedded interfaces, such as inter-processor communication link and serial interfaces, which facilitates its integration with other systems. The implementation of a straightforward localization algorithms based on the Phase Difference and the Time of Arrival techniques is also described. The ability of the developed system to localize underwater sensors was tested during sea trials.